PENERAPAN 5R PADA PENGELOLAAN PERPUSTAKAAN DUSUN KETANDAN, DESA MADUREJO, YOGYAKARTA - Kartinasari Ayuhikmatin Sekarjati (DHARMA BAKTI, 2020)
Community service extension program is carried out as one of the mandatoryactivities from the Institute to the community, which has the aim of applying scienceto the community. This counseling was conducted in the Ketandan Hamlet,Madurejo Village. This hamlet was chosen because it has great potential to bedeveloped. The hamlet has several sectors that can be developed, one of which ishuman resources (HR). The problem encountered in the HR sector was that themanager of the Village Library had problems in paying attention and managing thecomposition and neatness of the bookshelves owned by the "Citra Muda" Library inKetandan Hamlet, Madurejo Village.Based on the problems faced by Ketandan Hamlet, Madurejo Village, themethod to be applied is the 5R method. This method is able to solve problems relatedto layout and neatness management. This method applies 5 activities, namely seiri(concise), seiton (neat), seiso (rehearsal), seiketsu (caring) and shitsuke (diligent).The application of the 5R method is through direct education to the locationand providing examples of comparison images of the application of the 5R and notthe application of the 5R. Through this outreach, the community came to betterunderstand the importance of structure and neatness management, especially at the"Citra Muda" Library in Ketandan Hamlet, Madurejo Village